Efektivitas Penerapan Model Blended Learning Pasca Pandemi - Jumrah Jumrah; Abdul Razzaq; Asmawati Asmawati; Hamdana Hamdana (Mandalika Mathematics and Educations Journal, 2023)
This study aims to see the effectiveness of mathematics learning through the application of blended learning models. This type of research is pre-experimental research (One Group Pretest-Postest Design). The research population includes all students of the Mathematics Education Study Program Semester III STKIP Darud Da'wah wal Irsyad Pinrang and a sample, namely semester III. A class, which was selected using a simple random sampling technique. The variables studied are learning outcomes and student responses to mathematics learning with a blended learning model. The data analysis technique used is descriptive and inferential analysis techniques. The results showed (1) the completeness of mathematics learning outcomes after learning by applying an effective blended learning model with a percentage of completed students of 81%. (2) Student responses to learning through the application of blended learning models are in the good (positive) category with a large percentage of average responses agreeing and strongly agreeing reaching 81%. (3) Based on the significance level of 5% and df = 40 obtained Pvalue = 0.005 shows that the learning outcomes of groups of students who are taught through a blended learning model with those taught through conventional learning differ significantly from the category of strong effects.